Chitosan Nanoparticles: Synthesis, Properties, and Drug Delivery - Ghada Mohammed Saleh (World Journal of Experimental Biosciences, 2018)
Chitosan nanoparticles (CSNPs) represent one of the most widely researched platforms for allowing drug delivery in pharmaceuticals and they exhibit a high versatility in relation to the numerous uses that they can serve due to their unique qualities as biopolymers. Derived from chitin through deacetylation of that material, chitosan is biocompatible, biodegradable, exhibits mucoadhesive and cationic properties. The tunability of the phospholipid properties of the chitosan molecule (i.e., molecular weight, degree of deacetylation and charge density) makes it possible to design and produce CSNPs that are in the sub-micron to 1 micron size range or less in diameter. This review provides an in-depth coverage of the available literature and empirically investigates the physicochemical basis for the formation of CSNPs based on the following formation techniques: i) ionotropic gelation, ii) emulsification cross-linking, iii) nanoprecipitation, and iv) self-assembly. State-of-the-art characterization techniques, including the use of electron microscopy, dynamic light scattering or other particle sizing techniques, zeta potential, Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), and calorimetry (or thermal analysis), are addressed. Various mechanisms associated with cellular internalization and mucoadhesive/cell-cell adhesion interactions, as well as mechanisms of altering tight junctions and mechanisms by which CSNPs may be released from endosomes, are discussed. Safety assessments available on CSNPs encourage the researcher to consider this agent in the medical application in future projects.
Keywords: Chitosan nanoparticles; Drug delivery; Mucoadhesio, Nanoparticle characterizations